The Role of Multidisciplinary Primary Care Teams in the Effectiveness of Chronic Disease Prevention Programs in the Kingdom of Saudi Arabia - Moheteb, Lolowh Mohammed Al; Almassoud, Sultana Abdulrahman; Almutairi, Mubarak Aqeel; Alshamrani, Abu Bakr Ibrahim; Almutairi, Mohammed Shakhis; Alqahtani, Ghada Mohammed; Alanazi, Hanan Mohammed Zubayr; Alsaqer, Danah Mohammed; Almousa, Batool Hussain; Alanazi, Bandar Saeed (Journal of Posthumanism, 2024)
This systematic review investigates the role of multidisciplinary teams (MDTs) in the prevention and management of chronic diseases within primary care settings in Saudi Arabia from 2018 to 2024. The review highlights the increasing adoption of collaborative care models involving family physicians, nurses, and public health professionals to improve patient outcomes in chronic conditions such as diabetes, hypertension, and cardiovascular diseases. Findings emphasize the critical leadership role of family physicians in care coordination aligned with Saudi Vision 2030 healthcare transformation goals. Despite positive outcomes, challenges such as poor communication, unclear roles, and lack of institutional support impede the full effectiveness of MDTs. The review also underscores the necessity of integrating care across primary and secondary healthcare levels to optimize chronic disease management. Although local evidence remains limited, MDTs show promise in enhancing service delivery, patient satisfaction, and continuity of care. To maximize benefits, the study recommends focused capacity building, interprofessional training, structured team protocols, and robust health information systems. These strategies are essential for advancing chronic disease prevention and achieving universal health coverage in Saudi Arabia.